2019
DOI: 10.1038/s41598-019-41987-4
|View full text |Cite
|
Sign up to set email alerts
|

Strong and ductile AZ31 Mg alloy with a layered bimodal structure

Abstract: AZ31 Mg alloy was processed by accumulative roll-bonding (ARB) and hot rolling (HR), respectively, followed by annealing. Layered bimodal structures characterized by an alternative distribution of fine-grained layers and coarse-grained layers were obtained in the ARB samples, while mixed bimodal structures were achieved in the HR samples. The ARB samples have superior combinations of high strength and good elongation compared to the HR samples, indicating a clear effect of layered bimodal structures on mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…where σ YS is the yield stress, σ 0 is the resistance of the lattice to dislocation, K SY is the grain boundary strengthening, and D is the grain size (Lee et al, 2019). It could be observed that the recovered structure as the hard phase and the recrystallized structure as the soft phase (Luo et al, 2019). The soft layer of the recrystallized grains began to plastically deform during tensile test; however, the plastic deformation would be limited by the surrounding hard layer to produce strengthening from a constraint effect (Wang et al, 2018c).…”
Section: Resultsmentioning
confidence: 99%
“…where σ YS is the yield stress, σ 0 is the resistance of the lattice to dislocation, K SY is the grain boundary strengthening, and D is the grain size (Lee et al, 2019). It could be observed that the recovered structure as the hard phase and the recrystallized structure as the soft phase (Luo et al, 2019). The soft layer of the recrystallized grains began to plastically deform during tensile test; however, the plastic deformation would be limited by the surrounding hard layer to produce strengthening from a constraint effect (Wang et al, 2018c).…”
Section: Resultsmentioning
confidence: 99%
“…gradient microstructure, multilayers, bi-model structure etc.) has received more and more attention, because it can balance strength and toughness compared with uniform microstructure [83,84,85,86,87,88]. Thus, design of precipitation distribution by cold deformation and its influence on mechanical properties could be an important research direction in the further study.…”
Section: Strengthening Mechanism Via Combined Use Of Cold Deformatmentioning
confidence: 99%
“…In the research and development of strong and ductile Mg alloys, many routes have been explored encompassing a variety of processing and materials parameters [1,2]. Some examples of the processing routes explored include rolling [3,4], extrusion [5,6], and high pressure torsion (HPT) [7,8]. With regard to materials parameters, example approaches cover both the addition of alloying elements, including rare earths [9][10][11],…”
Section: Introductionmentioning
confidence: 99%